Pengaruh Kompetensi Kerja, Motivasi Kerja, dan Disiplin Kerja terhadap Kinerja Karyawan (Studi Empiris di Trio Plaza Magelang) - Sammy Rifah Sihombing; Dian Marlina Verawati; Axel Giovanni (ICON Publisher, 2026)
In an era of increasingly fierce business competition, employee performance has become one of the main factors in determining a company's success. Every company expects optimal results through good employee performance. This study was conducted to analyze the influence of work competence, work motivation, and work discipline on the performance of Trio Plaza Magelang employees. The sample in this study consisted of 127 respondents. To collect the sample, the researcher used simple random sampling by determining randomly. This study was quantitative. Data analysis was performed using descriptive statistical tests, validity and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing using SPSS version 26. The results of the study show that (1) work competence has a positive but not significant partial effect on employee performance, namely the t-count value is t-count 1.911 < t-table 1.984 and the significance value is 0.058. (2) Work motivation has a positive and significant partial effect on employee performance with a t-value of 5.704 > t-table 1.984 and a significance value of 0.000. (3) Work discipline has a positive and partially significant effect on employee performance with 5.726 > t-table 1.984 and a significance value of 0.000.